2019
DOI: 10.1109/tsp.2019.2928947
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Equalization With Feedforward Architectures for Massive MU-MIMO

Abstract: Linear data-detection algorithms that build on zero forcing (ZF) or linear minimum mean-square error (L-MMSE) equalization achieve near-optimal spectral efficiency in massive multi-user multiple-input multiple-output (MU-MIMO) systems. Such algorithms, however, typically rely on centralized processing at the base-station (BS) which results in (i) excessive interconnect and chip input/output (I/O) data rates and (ii) high computational complexity. Decentralized baseband processing (DBP) partitions the BS antenn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…Such feedforward architectures avoid the repeated exchange of information among clusters, which mitigates data transfer latency issues [9]. Furthermore, the theoretical analysis in [16] revealed that feedforward equalization architectures with linear algorithms are able to achieve the same or similar spectral efficiency as their centralized counterparts.…”
Section: B Decentralized Baseband Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…Such feedforward architectures avoid the repeated exchange of information among clusters, which mitigates data transfer latency issues [9]. Furthermore, the theoretical analysis in [16] revealed that feedforward equalization architectures with linear algorithms are able to achieve the same or similar spectral efficiency as their centralized counterparts.…”
Section: B Decentralized Baseband Processingmentioning
confidence: 99%
“…While the literature describes a number of feedforward DBP architectures and algorithms [7], [9], [16], a systematic tradeoff analysis under different system configurations and channel conditions is missing. Such a trade-off analysis, however, is critical to making design decisions for practical massive MU-MIMO systems that rely on DBP.…”
Section: Contributionsmentioning
confidence: 99%
See 3 more Smart Citations